Investigation of Effects of Abrasive Blasting on Fusion Welded Joints - Garg, Sangam (My University, 2015)
Fusion welding is a metal joining process used largely in industries. In fusion welding, high temperature melts the metal and joins the components. There are three types of fusion welding processes- Gas, Arc and High-energy beam welding. The present research focuses on Arc type- submerged arc welding (SAW), manual metal arc (MMA), tungsten inert gas (TIG), metal inert gas (MIG). Although fusion welding is widely used, there are many concerns about the weld quality. The problems faced are porosity, undercut, incomplete joint penetration, stresses etc. These defects affects the tensile strength, hardness, fatigue life of the joint. The welded parts also experiences melting and solidification process, dissolution of gases, distortion which leads to change in microstructural behavior and also changing the composition of the parts. To improve and enhance the properties abrasive blasting can be done. This study will attempt to provide the comparison of effects of abrasive blasting on fusion welded joints of low carbon and medium carbon steel. Input parameters are 4 different arc welding processes and 4 different shot blasting time periods. The output parameters will be Surface hardness, Tensile strength, Microstructure and fractography.
M.E. (Production Engineering)
Keywords: MIG; TIG; SAW; MMA; Abrasive Blasting; MED